Systematic review of psychosocial interventions for adult cancer patients and their family caregivers in Sub-Saharan Africa - Ting Guan; Yousef Qan'ir; Jamie L. Conklin; Chifundo Colleta Zimba; Agatha Bula; Wongani Jumbo; Kondwani Wella; Patrick Mapulanga; Samuel A.M. Bingo; Evelyn Chilemba; Jennifer Haley; Nilda Peragallo Montano; et al. (Taylor & Francis Group, 2023)
Cancer is becoming a public health issue in the Sub-Saharan Africa (SSA). This systematic review aims to synthesise psychosocial interventions and their effects on the health outcomes of adult cancer patients and their family caregivers in SSA. We identified eligible publications in English language from PubMed, Cumulative Index of Nursing and Allied Health Literature Plus with Full Text, Embase, APA PsycInfo, Scopus, and African Index Medicus databases. We included psychosocial interventions targeted adult cancer patients/survivors or their family caregivers in SSA. This review identified five psychosocial interventions from six studies that support adult cancer patients and their family caregivers in SSA. The interventions focused on providing informational, psycho-cognitive, and social support. Three interventions significantly improved quality of life outcomes for cancer patients and their caregivers. Significant gaps exist between the rapidly increasing cancer burdens and the limited psychosocial educational interventions supporting adult cancer patients and their families in SSA. The reviewed studies provide preliminary evidence on development and testing interventions that aim to improve patients' and caregivers' quality of life.